Pengaruh Penggunaan Pembelajaran Think Write Pair Shaire (TWPS) Berbantuan LMS terhadap Hasil dan Minat Belajar - Rakhmatul Ummah; Rizalul Fiqry (Department of Physics Education, Universitas Mataram, 2021)
Due to the spread and increasing number of positive cases due to the COVID-19 virus in Indonesia Especially Sape, Bima NTB, the Ministry of Education and Culture (Kemendikbud) recommends ways to reduce the spread of the virus by conducting online learning, this study explores the effect of cooperative learning on student learning outcomes in terms of interst in learning. The cooperative learning model used is Think Write Pair Share (TWPS) assisted by a learning management system (LMS) to lear during pandemic. The LMS used is Schoology. This research is an experimental study using a pre-test post-test control group design model. The research subjects consisted of two groups, namely the experimental group and the control group. All groups were given a pre-test (an instrument to measure learning outcomes) and a learning interest questionnaire using the ARCS model (attention, relevance, self-confidence) with thirty-four questions, the experimental group was given treatment in the form of teaching using Schoology-assisted cooperative learning TWPS. The control group was given conventional learning, after treatment, all groups were given a posttest and a learning interest questionnaire. The last stage is a data processing and data analysis using ANCOVA, the result is that Schoology assisted TPS cooperative learning can improve student learning outcomes with a significance level of 0.005.